Pengaruh lama perebusan dan tingkat konsentrasi bahan kyuring : garam, gula merah, jahe dan serai terhadap kualitas uji hedonik abon ayam broiler - Kastalani Kastalani; Yemima Yemima; Agus Winata (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This study aims to determine effect of boiling time, concentration of curing materials: salt, palm sugar, ginger and lemon grass, and interaction between boiling time and concentration of curing materials on the hedonic quality test of shredded broiler chicken. This research used Completely Randomized Design (CRD) with factorial pattern with 2 factors namely factor boiling time (P) with 3 levels of treatment and factor concentration of curing materials (C). The observed parameters include colour, smell and flavour of shredded broiler chicken performed using the panels to assign values of the samples characteristic. The research showed the hedonic quality test of colour and smell characteristics of shredded broiler chicken had no significant effect, while the hedonic quality test of flavour characteristic had very significant effect. Key words : Boiling time, curing, hedonic test, shredded broiler chicken.